Disconnected in a connected world: improving digital literacies instruction to reconnect with each other, ideas, and texts - Marangell, Joseph; Randall, Régine (Education Sciences, 2025)
This commentary addresses a problem of practice related to student disengagement in technology-rich classrooms, where learners are digitally connected but socially and academically disconnected. Although not an empirical study, the commentary draws on instructional examples from secondary- and graduate-level teaching. The authors examine how digital literacy instruction can strengthen engagement, reading comprehension, and ethical participation in online environments. The article highlights strategies such as the workshop model, multimodal composition, digital content curation, and the use of mentor texts to support critical thinking and collaborative learning. These practices aim to develop students’ analytical skills, awareness of audience, and recognition of their own positionality in digital spaces. Across courses, the authors reflected on increased student engagement when digital tools were used not simply for task completion but to support inquiry, discourse, and authentic creation for real audiences.
Keywords: Comprehension; Computer science; Critical thinking; Digital literacy; Disengagement theory; Linguistics; Literacy; Mathematics education; Pedagogy; Psychology; Reading (process); Reading comprehension; Sociology; Student engagement; Task (project management); dept.cur